Vaccinomics-based next-generation multi-epitope chimeric vaccine models prediction against Leishmania tropica - a hierarchical subtractive proteomics and immunoinformatics approach - Aiman, Sara; Ahmad, Abbas; Khan, Azmat Ali; Alanazi, Amer M.; Samad, Abdus; Ali, Syed Luqman; Li, Chunhua; Ren, Zhiguang; Khan, Asifullah; Khattak, Saadullah (Frontiers in Immunology, 2023)
Leishmania tropica is a vector-borne parasitic protozoa that is the leading cause of leishmaniasis throughout the global tropics and subtropics. L. tropica is a multidrug-resistant parasite with a diverse set of serological, biochemical, and genomic features. There are currently no particular vaccines available to combat leishmaniasis. The present study prioritized potential vaccine candidate proteins of L. tropica using subtractive proteomics and vaccinomics approaches. These vaccine candidate proteins were downstream analyzed to predict B-and T-cell epitopes based on high antigenicity, non-allergenic and non-toxic characteristics. The top-ranked overlapping MHC-I, MHC-II, and linear B-cell epitopes were prioritized for model vaccine designing. The lead epitopes were linked together by suitable linker sequences to design multi-epitope constructs. Immunogenic adjuvant sequences were incorporated at the N-terminus of the model vaccine constructs to enhance their immunological potential. Among different combination of constructs, four vaccines designs were selected based on their physicochemical and immunological features. The tertiary structure models of the designed vaccines constructs were predicted and verified. The molecular docking and molecular dynamic (MD) simulation analyses indicated that the vaccine design V1 demonstrated robust and stable molecular interactions with toll-like receptor 4 (TLR4). The top-ranked vaccine construct model-IV demonstrated significant expressive capability in the E. coli expression system during in-silico restriction cloning analysis. The results of the present study are though intriguing; nevertheless, experimental bioassays are required to validate the efficacy of the predicted model chimeric vaccine.